2017
DOI: 10.1097/dss.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of VYC-15L, a Hyaluronic Acid Filler for Lip and Perioral Enhancement: One-Year Results From a Randomized, Controlled Study

Abstract: VYC-15L was safe and effective for lip and perioral enhancement, with treatment effects lasting through 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 7 publications
2
51
0
Order By: Relevance
“…The most commonly used assessment scale was the photonumeric Lip Fullness Scale (LFS). Three different LFS were used: Medicis LFS, Allergan LFS, and Lip Fullness Grading Scale . For the number of points on the scales and its descriptive definitions, see Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used assessment scale was the photonumeric Lip Fullness Scale (LFS). Three different LFS were used: Medicis LFS, Allergan LFS, and Lip Fullness Grading Scale . For the number of points on the scales and its descriptive definitions, see Table .…”
Section: Resultsmentioning
confidence: 99%
“…In four randomized controlled studies, the authors defined severity and duration of AEs. Most subjects reported treatment‐related AEs as mild (range 71%‐88%) or moderate (range 11%‐16%) in severity.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of effects for hyaluronic acid fillers has been reported at 3 to 12 months, 1 year,18 months, and 2 years . A recent study of the use of injectable hyaluronic acid gel to correct volume loss of facial temporal fossa showed that the effects of the gel persisted at least 12 months in 98% of subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Because the lips and perioral regions experience constant movement, selecting a product suitable for this area is crucial for achieving a natural‐looking result. Multiple studies have proven the efficacy and safety of different HA filler products for lip and perioral injection, such as nonanimal stabilized HA, or NASHA (Restylane® Vital and Restylane® Silk, Galderma); Hyacross HA (Juvederm® Ultra and Ultraplus, Allergan); and Vycross HA (Juvéderm® Volift™, Volbella™, and Volite™, Allergan) 8‐13 . Other HA products commonly used for lip augmentation or enhancement include Restylane® Refyne™ and Restylane® Kysse™ (Galderma); Stylage® LIPS (Vivacy); and Beletero ® Shape or Beletero ®Contour (Merz).…”
Section: Product Selectionmentioning
confidence: 99%